Cardiocerebrovascular risk in sensorineural hearing loss: results from the National Health and Nutrition Examination Survey 2015 to 2018 - Zheng, Jianrong; Cheng, Yajing; Zhan, Ying; Liu, Cong; Lu, Bihua; Hu, Jun (Frontiers in Neurology, 2023)
Objective This study aims to determine whether the risks of cardiocerebrovascular disease are relevant to sensorineural hearing loss (SNHL) based on a national database. Methods A total of 1,321 participants aged from 18 to 69 with complete data including medical history and audiometry from the NHANES database (2015–2018) were analyzed. All included participants had available hearing data and the average thresholds of the hearing data were measured and calculated as low-frequency pure-tone average (LFPTA; 500, 1,000, and 2,000 Hz) and high-frequency pure-tone average (HFPTA; 3,000, 4,000, 6,000, and 8,000 kHz). SNHL was defined as an average pure tone of more than or equal to 20 dB in at least one better ear. Multivariable models to assess the association between cardiocerebrovascular risks and SNHL were used in this study. Results The prevalence of stroke was 1.6% in individuals with SNHL and 0.4% in individuals without SNHL (p = 0.023). A higher cardiovascular risk score was observed in SNHL patients compared to participants without SNHL (1.58 vs. 0.90, p < 0.001). Stroke was associated with a 3.67-fold increase in the risk of SNHL (95% CI: 1.12–12.00, p = 0.032) in univariable logistic regression, and the association (OR = 4.22, 95%CI = 1.28–13.93, p = 0.020) remained significant after adjusting for several covariates. Multivariable logistic regression models indicated a positive correlation between cardiovascular risk and SNHL (OR = 1.66, 95% CI = 1.40–1.96, p < 0.001), but no significant relationship was shown with all covariates adjusted. However, significant associations were found between SNHL and both age and sex in both univariable and multivariable logistic regression models. Conclusion Our findings suggested that a higher cardiocerebrovascular risk burden was associated with an increased risk of SNHL, and the relationship may be influenced by age and sex. Future longitudinal studies are needed to investigate the mechanistic and pathologic vascular hypothesis of SNHL.